Affimers targeting proteins in the cardiomyocyte Z-disc: Novel tools that improve imaging of heart tissue - Parker, Francine; Tang, Anna A. S.; Rogers, Brendan; Carrington, Glenn; dos Remedios, Cris; Li, Amy; Tomlinson, Darren; Peckham, Michelle (Frontiers in Cardiovascular Medicine, 2023)
Dilated Cardiomyopathy is a common form of heart failure. Determining how this disease affects the structure and organization of cardiomyocytes in the human heart is important in understanding how the heart becomes less effective at contraction. Here we isolated and characterised Affimers (small non-antibody binding proteins) to Z-disc proteins ACTN2 (α-actinin-2), ZASP (also known as LIM domain binding protein 3 or LDB3) and the N-terminal region of the giant protein titin (TTN Z1-Z2). These proteins are known to localise in both the sarcomere Z-discs and the transitional junctions, found close to the intercalated discs that connect adjacent cardiomyocytes. We use cryosections of left ventricles from two patients diagnosed with end-stage Dilated Cardiomyopathy who underwent Orthotopic Heart Transplantation and were whole genome sequenced. We describe how Affimers substantially improve the resolution achieved by confocal and STED microscopy compared to conventional antibodies. We quantified the expression of ACTN2, ZASP and TTN proteins in two patients with dilated cardiomyopathy and compared them with a sex- and age-matched healthy donor. The small size of the Affimer reagents, combined with a small linkage error (the distance from the epitope to the dye label covalently bound to the Affimer) revealed new structural details in Z-discs and intercalated discs in the failing samples. Affimers are thus useful for analysis of changes to cardiomyocyte structure and organisation in diseased hearts.